The Relationship between Current Account Deficit, Economic Growth and Oil Prices in Developing Countries - Yessymkhanova, Zeinegul; Khamitova, Dariga; Bakytgul, Utegulova; Azretbergenova, Gulmira (International Journal of Energy Economics and Policy, 2025)
In this study, the relationship between current account deficit, economic growth and oil prices for 5 countries (Argentina, Indonesia, India, Mexico and Turkey) between 1980–2023 was examined using panel data analysis method. First, unit root tests were performed on the variables and stationarity was determined. Since the current account deficit, economic growth and oil price variables were stationary in their first degree differences, Pedroni and Kao Panel Cointegration Tests were performed and it was determined that the variables were cointegrated. After the cointegration test, Dumitrescu and Hurlin Panel Causality Test was performed and one-way causality was determined from economic growth to current account deficit and oil prices, and from oil prices to current account deficit.